Prevalence and associated factors of insomnia symptoms among doctors and nurses under the context of high prevalence of multiple infectious diseases: a cross-sectional study - Chen, Xu; Wang, Bin; Wang, Yu; He, Surui; Liu, Dongmei; Yan, Dongmei (Frontiers in Public Health, 2024)
Introduction: Insomnia symptoms are prevalent among healthcare workers and represent a potential public health problem. However, there is currently insufficient evidence on insomnia symptoms among doctors and nurses under the context of high prevalence of multiple infectious diseases after the pandemic in China. The purpose of this study was to analyze the prevalence of insomnia symptoms among doctors and nurses in third-grade class-A general hospitals under the context of high prevalence of multiple infectious diseases, and to explore the influence of demographic characteristics, work-related factors, health and lifestyle-related factors on insomnia symptoms. Methods: An institution-based cross-sectional survey was conducted among doctors and nurses in two third-grade class-A general hospitals. A structured questionnaire was used to collect information on demographic characteristics, work-related factors, health and lifestyle-related factors, and insomnia symptoms among doctors and nurses. Multivariate logistics regression analysis was applied to identify factors significantly associated with insomnia symptoms among doctors and nurses, respectively. Results: A total of 1,004 participants were included in this study, including 503 doctors and 501 nurses. The prevalence of insomnia symptoms in doctors and nurses was 47.7% and 51.3%, respectively. Multivariate logistics regression analysis showed that workplace violence (OR: 1.631, 95% CI: 1.050-2.532), doctor-patient relationship (OR: 1.603, 95% CI: 1.049-2.450), chronic pain (OR: 4.134, 95% CI: 2.579-6.625), chronic disease (OR:1.825, 95% CI: 1.164-2.861), and anxiety symptoms (OR: 2.273, 95% CI: 1.357-3.807) were associated factors with insomnia symptoms in doctors. Education (OR: 0.301, 95% CI: 0.106-0.851), service years (OR: 1.978, 95% CI: 1.304-3.002), weekly working hours (OR: 1.694, 95% CI: 1.061-2.705), chronic pain (OR: 5.359, 95% CI: 3.241-8.860), and anxiety symptoms (OR: 2.472, 95% CI: 1.478-4.136) were associated factors with insomnia symptoms in nurses. Conclusion: The prevalence of insomnia symptoms among doctors and nurses was high, and affected by many factors. This information can inform tailored interventions to insomnia symptoms by doctors and nurses who play an important role in public health.